1993
DOI: 10.1111/j.1751-1097.1993.tb02261.x
|View full text |Cite
|
Sign up to set email alerts
|

SPECTRAL FORMS AND ORIENTATION OF BACTERIOCHLOROPHYLLS c AND α IN CHLOROSOMES OF THE GREEN PHOTOSYNTHETIC BACTERIUM Chloroflexus aurantiacus

Abstract: Spectral forms of bacteriochlorophyll (Bchl) in chlorosomes were analyzed by linear dichroism, circular dichroism (CD), and deconvolution of these spectra. Isolated chlorosomes were embedded in polyacrylamide gels and compressed unidirectionally (along the x-axis) while allowing the gel to stretch in another direction (along the z-axis). The chlorosomes were aligned three-dimensionally due to their Rat oblong shape; the longest axis was presumed to parallel the z-axis, its shortest axis was presumed to paralle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
54
0

Year Published

1994
1994
2008
2008

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(62 citation statements)
references
References 23 publications
8
54
0
Order By: Relevance
“…We found six fluorescence components in this study and suggested the presence of a short wavelength form of Bchl c. The last one may correspond to Bchl ~727 which we observed by LD spectra [6]. Besides these, Bchl a806 [24] is known to be present.…”
Section: Heterogeneity Of Antenna Componentssupporting
confidence: 56%
See 3 more Smart Citations
“…We found six fluorescence components in this study and suggested the presence of a short wavelength form of Bchl c. The last one may correspond to Bchl ~727 which we observed by LD spectra [6]. Besides these, Bchl a806 [24] is known to be present.…”
Section: Heterogeneity Of Antenna Componentssupporting
confidence: 56%
“…Thus, the number of spectral components has now been estimated to eight in C. aurantiacus. Two major Bchl c's (Bchl ~727 and Bchl ~744) [6] and the third fluorescence component (Bchl ~766 or F781, in this study) were assigned to be constituents of chlorosomes. Presence of two baseplate Bchl's a (F810 and F819 in this study) are consistent with our previous report [8].…”
Section: Heterogeneity Of Antenna Componentsmentioning
confidence: 71%
See 2 more Smart Citations
“…We refrain from an extensive discussion of all antenna types, as excellent reviews can be found elsewhere. [19] Antennas contain high concentrations of pigment molecules, including chloro- While several models have been proposed for the pigment organization in chlorosomes, a common characteristic is the existence of aggregates of bacteriochlorophyll c, either rods of 5-10 nm in diameter and 100-200 nm in length [22,23,24,25,26] or semicrystalline lamellar sheets. [20] The regular structure of Bchl c van der Waals bonded aggregates leads to strong exciton coupling and a red-shift in absorption.…”
Section: Photosynthetic Antenna Complexesmentioning
confidence: 99%